PUTUSAN HAKIM TERHADAP PERKARA GHAIB PADA CERAI GUGAT DI PENGADILAN AGAMA METRO - Ulfa Fatimatu Zahra; Sudirman (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
This study analyzes the judge's consideration in deciding supernatural cases in divorce lawsuits at the Metro Religious Court through Decision Number 230/Pdt.G/2023/PA.Mt. The main problem is how the judge decides the supernatural divorce case when the husband leaves his wife for less than two years, even though Article 116 letter (b) of the KHI requires a minimum of two consecutive years. Using normative legal research methods with a legislative and case approach, this study analyzes court decisions and Islamic legal literature. The results of the study show that judges use a substantive-protective approach by integrating legal-formal and philosophical aspects based on the rules of fiqhiyyah